2017
DOI: 10.1016/j.envres.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature and risk of cardiovascular events at labor and delivery: A case-crossover study

Abstract: Background Extreme ambient temperatures are linked to cardiac events in the general population, but this relationship is unclear among pregnant women. We estimated the associations and attributable risk between ambient temperature and the risk of cardiovascular event at labor/delivery, and investigated whether these associations vary by maternal race/ethnicity. Methods We identified 680 women with singleton deliveries affected by cardiovascular events across 12 US sites (2002–2008). Average daily temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
(53 reference statements)
2
22
0
2
Order By: Relevance
“…Environmental exposure, such as ambient air pollution and extreme temperatures, is an important but underappreciated risk factor contributing to the development and severity of CVDs [4]. Accumulating evidence from epidemiological studies has linked environmental exposure to increased risk of CVDs morbidity [5][6][7][8][9][10][11][12]. However, evidence of the effect of a complex mixture of environmental exposure on CVDs morbidity is still limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental exposure, such as ambient air pollution and extreme temperatures, is an important but underappreciated risk factor contributing to the development and severity of CVDs [4]. Accumulating evidence from epidemiological studies has linked environmental exposure to increased risk of CVDs morbidity [5][6][7][8][9][10][11][12]. However, evidence of the effect of a complex mixture of environmental exposure on CVDs morbidity is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) are the leading cause of death worldwide; about 17.9 million deaths were attributable to CVDs in 2016, representing approximately 31% of all global deaths in that year [1]. Even though behavioral factors, including physical inactivity, smoking, unhealthy diets and obesity, are well-known risk factors for CVDs, a large body of studies have indicated that environmental exposure [2][3][4], such as ambient air pollution [5][6][7][8][9] and temperature variability [10][11][12], also makes a significant contribution to CVDs, resulting in increased risk of morbidity. For example, using conditional logistic regression models, Liu et al [13] conducted a multi-city study in 26 Chinese cities, and the results showed that elevated concentrations of sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), carbon monoxide (CO), and ozone (O 3 ) were associated with increased risk of hospitalization for heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental exposure, such as ambient air pollution and extreme temperatures, is an important but underappreciated risk factor contributing to the development and severity of CVDs [4]. Accumulating evidence from epidemiological studies has linked environmental exposure to increased risk of CVDs morbidity [5][6][7][8][9][10][11][12]. However, evidence of the effect of a complex mixture of environmental exposure on…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular diseases (CVDs) are the leading cause of death worldwide; about 17.9 million deaths were attributable to CVDs in 2016, representing approximately 31% of all global deaths in that year [1]. Even though behavioral factors, including physical inactivity, smoking, unhealthy diets and obesity, are well-known risk factors for CVDs, a large body of studies have indicated that environmental exposure [2][3][4], such as ambient air pollution [5][6][7][8][9] and temperature variability [10][11][12], also makes a significant contribution to CVDs, resulting in increased risk of morbidity. For example, using conditional logistic regression models, Liu et al [13] conducted a multi-city study in 26 Chinese cities, and the results showed that elevated concentrations of sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), carbon monoxide (CO), and ozone (O 3 ) were associated with increased risk of hospitalization for heart failure.…”
mentioning
confidence: 99%
“…Even though behavioral factors, including physical inactivity, smoking, unhealthy diets and obesity, are the well-known risk factors for CVDs, a large body of studies have indicated that environmental exposure [4], such as ambient air pollution [5][6][7][8][9] and temperature variability [10][11][12], also makes significant contributions to CVDs, resulting in increased risk of morbidity. For example, using conditional logistic regression models, Liu et al [13] conducted a multi-city study in 26 Chinese cities, and the results showed that elevated concentrations of sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), carbon monoxide (CO), and ozone (O 3 ) were associated with increased risk of hospitalization for heart failure.…”
Section: Introductionmentioning
confidence: 99%